2020
DOI: 10.1038/s41598-020-58970-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic value of SOX11 in childhood acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia is marked by aberrant transcriptional features that alter cell differentiation, self-renewal, and proliferative features. We sought to identify the transcription factors exhibiting altered and subtype-specific expression patterns in BALL and report here that SOX11, a developmental and neuronal transcription factor, is aberrantly expressed in the ETV6-RUNX1 and TCF3-PBX1 subtypes of acute B-cell leukemias. We show that a high expression of SOX11 leads to alterations of gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…It has been reported that the high expression of SOX11 leads to alterations of gene expression that are typically associated with cell adhesion, migration, and differentiation. Furthermore, its expression marks a group of patients with good outcomes [ 40 ]. Furthermore, Huang et al demonstrated that AML1-ETO-fused protein triggers the epigenetic silencing of the EYA4 gene, contributing to leukemogenesis in t (8;21) AML.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the high expression of SOX11 leads to alterations of gene expression that are typically associated with cell adhesion, migration, and differentiation. Furthermore, its expression marks a group of patients with good outcomes [ 40 ]. Furthermore, Huang et al demonstrated that AML1-ETO-fused protein triggers the epigenetic silencing of the EYA4 gene, contributing to leukemogenesis in t (8;21) AML.…”
Section: Discussionmentioning
confidence: 99%
“…The formalin-fixed and paraffin-embedded bone marrow trephine biopsy samples of the pediatric B-ALL patients were collected into a tissue microarray (TMA) with 1.5 mm punches (see also [ 21 ]), and 4-micrometer TMA sections were used for immunohistochemistry. An appendix was used as a control material for the IGF2BP3 and CD19/Ki-67 immunostainings.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of BCL6 and pSTAT5 was semiquantitatively graded as negative when antigen was expressed in under 20% of leukemic blasts, and positive when expressed in over 20%. Clinical data and the flow cytometry data (e.g., CD34 expression) were retrieved from patient hospital records gathered as described previously [ 21 ]. The flow cytometry results were graded as either negative or positive.…”
Section: Methodsmentioning
confidence: 99%
“…17 For cases lacking the genetic subtype information, fluorescence in situ hybridisation analysis was performed on either BM aspiration samples or formalin fixed and paraffin embedded (FFPE) samples. 18…”
Section: Bone Marrow Biopsies and Associated Clinical Datamentioning
confidence: 99%
“…Three independent RNA expression datasets were used to analyse BCL6 gene expression as previously described: 18 (1) the Hemap dataset, which is a microarray dataset of 36 haematological malignancies that includes 6832 samples, including 662 paediatric and 642 adult B-ALL cases collected from different original studies that represent both high risk cohorts and those that include also common good prognosis subtypes; 19,20 (2) the PanALL study dataset, an RNA-sequencing dataset (n=1988), which includes 1234 paediatric and 754 adult B-ALL cases from different patient cohorts and therapy risk groups; 21 (3) a Nordic dataset, which consists of RNA-sequencing data from 115 paediatric B-ALL cases that represent cases diagnosed between the years 1996 and 2010 from different therapy risk groups. 22 The pre-BCR 'metagene' signature was studied in the Hemap and PanALL datasets, and included IGLL1, IGLL3, VPREB1, VPREB3, IGHM, SYK and ZAP70 genes, as described by Geng et al 9 Normalisation of the mRNA expression values has been described previously for the Hemap dataset 19,20 and the PanALL dataset.…”
Section: Gene Expression Datasetsmentioning
confidence: 99%